2015
DOI: 10.5642/jhummath.201502.06
|View full text |Cite
|
Sign up to set email alerts
|

On Similarities and Differences Between Proving and Problem Solving

Abstract: A link between proving and problem solving has been established in the literature [5,21]. In this paper, I discuss similarities and differences between proving and problem solving using the Multidimensional Problem-Solving Framework created by Carlson and Bloom [2] with Livescribe pen data from a previous study [13]. I focus on two participants' proving processes: Dr. G, a topologist, and L, a mathematics graduate student. Many similarities between the framework and the proving processes of Dr. G and L were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…First, answers are more readily available to students in the age of ubiquitous access to the internet (Linshi, 2016;Williams, 2020). Second, if problem solving is improved on in class, the products that result will improve due to students' checking and re-evaluating their own work -an action that is common in the problem-solving literature (Savić, 2015b). Liljedahl (2004) stated that checking is where the "solver reengages with the problem," and that solution can yield much more exploration and learning (Knuth, 2002).…”
Section: Background Literaturementioning
confidence: 99%
“…First, answers are more readily available to students in the age of ubiquitous access to the internet (Linshi, 2016;Williams, 2020). Second, if problem solving is improved on in class, the products that result will improve due to students' checking and re-evaluating their own work -an action that is common in the problem-solving literature (Savić, 2015b). Liljedahl (2004) stated that checking is where the "solver reengages with the problem," and that solution can yield much more exploration and learning (Knuth, 2002).…”
Section: Background Literaturementioning
confidence: 99%
“…Schoenfeld (1985) (Knapp, 2003). Harel & Sowder (1998, 2007 Para Savic (2015) la demostración matemática y la resolución de problemas se superponen y que al revisar la literatura sobre resolución de problemas se pueden describir aspectos de la demostración, ya que esta última es una consecuencia de la resolución de problemas.…”
Section: Palabras Claveunclassified
“…There was a relationship between the proving and problem solving. According to Savic (2015) there was an overlap between the proving and problem solving, while Downs et al (2013) suggested that the problem solving aspects were within the proving. The test item for proving could also be seen as an item for problem solving.…”
Section: Introductionmentioning
confidence: 99%